2008
DOI: 10.1227/01.neu.0000318180.80040.d0
|View full text |Cite
|
Sign up to set email alerts
|

The Utility and Feasibility of Business Training for Neurosurgeons

Abstract: New tools from advances in business are available which have been invaluable to corporations and may be helpful to neurosurgeons wanting to improve efficiency and maintain competitive advantage. Business training is available to neurosurgeons through a variety of routes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Providing the best possible neurosurgical services with available facilities can help most of the patients living at smaller places to have access to neurosurgical services, who often fail to travel to distant places due to various reasons, the most important of which is usually financial implications. [34][35][36] Manual instruments work on basic physics principles and one should analyze the act of bone work required at the deep-seated surgical corridors. Humans are most proficient in using their hands mainly because use of hand starts even before birth (intrauterine stage).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing the best possible neurosurgical services with available facilities can help most of the patients living at smaller places to have access to neurosurgical services, who often fail to travel to distant places due to various reasons, the most important of which is usually financial implications. [34][35][36] Manual instruments work on basic physics principles and one should analyze the act of bone work required at the deep-seated surgical corridors. Humans are most proficient in using their hands mainly because use of hand starts even before birth (intrauterine stage).…”
Section: Discussionmentioning
confidence: 99%
“…This is the responsibility of the experienced neurosurgeons working at well-equipped centres to explain and propagate detailed technical nuances of using manual instruments which will help in increasing access to neurosurgical care at large part of the world where people struggle to get even basic neurosurgical services. 26,[34][35][36] A chisel has two surfaces, one flat and another slanting. A vertical tap on the top of the chisel will cut the bone towards an angle of slanting edge, whereas, an osteotome will always cut in the This document was downloaded for personal use only.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Deficiencies in socioeconomic training for neurosurgeons have been described for many years. 2,[42][43][44][45] The socioeconomic training program developed by Youngerman et al 29 demonstrated this shortcoming might be remediated with a milestone-based curriculum. The importance of other nontechnical skills such as communication, 46,47 patient counseling, professionalism, 48 and leadership have been emphasized in the literature, though few studies addressed interventions with objective outcomes.…”
Section: Nontechnical Skillsmentioning
confidence: 99%
“…Department chairs, group administrators, and neurosurgical spokespersons who administer and represent group interests are vital to our organizational integrity and demand special preparation to assume tasks in modern environments. Giller (7) has addressed this issue. Business topics related to neurosurgeons include: 1) change management, 2) marketing, 3) negotiation, 4) process, 5) accounting and finance, 6) management and leadership, 7) strategy, 8) entrepreneurialism, and 9) organization and vision.…”
Section: The Reinvention Of the Neurosurgeonmentioning
confidence: 99%